An Inquiry Into Language-Switching in Second Language Composing Processes - Qi, Donald S (Canadian modern language review, 1998)
Investigates factors influencing language-switching behavior in the thinking processes of a bilingual person engaged in second-language writing, based on review of literature and a case study in which an individual performs three tasks using think-aloud protocols: text composition in English (second language); written translation from Chinese (first language); and mathematical problem solving in English. (Author/MSE)